Death comes as the end - Christie, Agatha (HarperCollins, 2017)
It is Egypt, 2000 BC, where death gives meaning to life. At the foot of a cliff lies the broken, twisted body of Nofret, concubine to a Ka-priest. Young, beautiful and venomous, most agree that she deserved to die like a snake. Yet Renisenb, the priest's daughter, believes that the woman's death was not fate, but murder. Increasingly, she becomes convinced that the source of evil lurks within her own father's household. As the wife of an eminent archaeologist, Agatha Christie took part in several expeditions to the Middle East. Drawing upon this experience and exhaustive research, she wrote this serial killer mystery laid in Egypt 4000 years ago.